P102 Sweat chloride is not a useful marker of clinical response to Ivacaftor. (14th November 2013) - Barry, PJ; Flight, WG; Biesty, J; Clough, D; Small, I; Johnson, S; Brennan, AL; Bright-Thomas, RJ; Webb, AK; Jones, AM; Horsley, AR
Abstract : Introduction and Objectives: The development of the targeted CFTR potentiator Ivacaftor has significantly altered the landscape for cystic fibrosis (CF) therapeutics, and heralds the arrival of personalised medicine in this condition. Data from Phase III clinical trials have been encouraging and suggested that the use of Ivacaftor results in a normalisation of sweat chloride and significant increases in pulmonary function and weight in suitable patients. As part of the commissioning requirements for Ivacaftor in the UK, sweat chloride changes represent the major criteria for continuing prescription, with a reduction of 30% or reduction below 60 mmol/L proposed as cut-offs for continuation of therapy. We aimed to assess the relationship of sweat chloride to clinical outcomes in patients receiving Ivacaftor treatment. Methods: All Ivacaftor naïve patients who carried the G551D mutation were contacted to enable the commencement of the medication. Baseline sweat chloride was recorded, and repeated at 2 months. Baseline pulmonary function, height and weight were recorded and repeated at monthly visits for 3 months. Results: To date 24 of 27 suitable subjects have commenced Ivacaftor. Mean FEV1 % predicted was 64.3% predicted at Ivacaftor commencement and mean BMI was 22.1 kg/m 2 . Mean FEV1 percent predicted increased in absolute terms by 8.9% at 1 month and 8.7% at 3 months (p < 0.001 at both time points). Mean BMI improved to 22.7 kg/m 2 at 1 month and 23.0 kg/m 2 at 3 months (p = 0.002, 0.003 respectively). There was a significant fall in sweat chloride at 2 months (median 114 to 51 mmol/L, p < 0.001). Improvement in sweat chloride was not correlated in absolute or relative terms with improvements in pulmonary function or BMI. Four subjects with a mean absolute FEV1 improvement of 14.5% had sweat chloride responses not meeting pre-specified criteria at 2 months. Two of these subjects had a subsequent repeat test meeting continuation criteria. In one subject a suboptimal response was attributed to the omission of a single dose. Conclusions: The use of sweat chloride as a surrogate for clinical efficacy and a criterion for drug continuation is not supported by this data. Sweat chloride may be a marker of 100% adherence to therapy.